ANALYSIS SUFFIXES ON REPORT TEXT “WASHINGTON D.C” - Rajagukguk, Fretty Riana; Purba, Irene Stefani Mutiara; Sitepu, Rachel Yolanda; Sitanggang, Anita (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2022)
Suffix is one component that can be used to form new words in English. The suffix used in this case is a beginning suffix. The purpose of this study to finding the form, function and meaning of the beginning suffix found in "WASHINGTON DC" in the Report Text. The form, function and meaning of the beginning affixes found are classified According to the theory by Plag (2002) in his book "Word-Formation in English." The results of this study indicate that there are four types of suffix, namely "nominal suffixes," "verb suffixes," "adjectival suffixes" and "adverbial suffixes." In this study the author uses qualitative research, to analyze the suffix in the report text "Washington DC". Qualitative research as the study of the real of phenomena mainly suitable for answer the questions of why the thing is not inspect, and focusing on intervention improvement. It can be said that there are four forms of suffixes found in the data source, namely nominal suffix, verbal suffix, adjectival suffix and adverbial suffix. In Indonesia there are seven types of suffixes, namely: -an, -I, -kan, -kah, -ku, -mu, -nya, -pun. Research findings showed that beginning suffixes was found in the washingthon D.C., they are suffix -al, -s, -ist, -ion, -ing, -ed, -ly, - ous, -ence, in Indonesia we found suffixs -kan, -an, -nya.